Efektivitas Jeruk Lemon (Citrus limon Linn) terhadap Staphylococcus epidermidis: Effectiveness of Lemon (Citrus limon Linn) against Staphylococcus epidermidis - Hartin, Ellyce; Rini, Chylen Setiyo (Medicra (Journal of Medical Laboratory Science/Technology), 2019)
Acne or acne vulgaris is the one of the skin diseases that often appear in adolescents and adults. Acne is often associated with the condition of the body, either in stress condition because of sad or being happy. Acne can be caused by genetic, cosmetic, and bacterial factors. Bacteria that can cause swelling diseases is Staphylococcus epidermidis. For overcoming acne, people can use traditional medicine such as lemon juice (Citruslimon Linn). The main composition that exists in lemon juice (Citrus limon Linn) is citric acid that acts as an antimicrobial against bacteria present in acne. This study aims to determine the influence of lemon juice lime juice (Citrus limon Linn) against Staphylococcus epidermidis. This research is an experimental laboratory that use disc disk method or Kirby bauer method with concentration 0%, 12,5%, 25%, 50% and 100%. The result of the study shows that lemon lime juice (Citrus limon Linn) at 25% concentration already have a transparent zone around the paper disc about 12.1 mm and have low effectivity to secure Staphylococcus epidermidis. The high concentration of lemon juice will increase the inhibitory power produced by lemon juice (Citrus limon Linn).